An update to estimates of human capital in New Zealand. Background paper to Te Tai Waiora: Wellbeing in Aotearoa New Zealand 2022 - Margaret Galt (New Zealand Government, The Treasury, 2023)
Human capability is one of the four aspects of wealth in the Treasury's Living Standards Framework. Combined with the other three aspects - the natural environment, physical and financial capital, and social cohesion, it underpins both current and future wellbeing. Human capability is defined as 'people's knowledge, physical and mental health, including cultural capability'. It would be ideal if we could measure the total contribution to wellbeing of all of these aspects but, at the moment, there is no generally accepted methodology to do this, so it is not covered in this note. Instead, the methodology used widely in the literature measures only the labour market value of the knowledge portion, by looking at lifetime earnings associated with different levels of education. We have called this component 'human capital' in this note.
Keywords: 330; Humankapital; Qualifikation; Messung; Neuseeland